Upaya Melatih Kemampuan Membaca dan Literasi Digital Siswa Sekolah Dasar melalui Kegiatan Latihan ANBK - Naomi Dias Laksita Dewi; Nabilah Nu Jannah; Chelsealia Imraatun Hasanah; Imelda Tri Ayu Restianto; Ahmad Ramadhany; Syafina Nafa Sasita Kirana; Dinda Anisatul Hasanah; Muhammad Desta Kurniawan Saputra; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This Community Service (PkM) program was motivated by the low early reading ability of grade 1 students and limited digital literacy skills of grade 5 students at SDN Curahdami 2, Bondowoso, which affected their learning process and readiness for the Computer-Based National Assessment (ANBK). The program aimed to improve pre-literacy, beginning reading skills, and digital literacy through structured ANBK training activities. The implementation methods included initial observation, intensive mentoring, and hands-on practice conducted over seven weeks using letter tables, reading modules, phonics cards, ANBK practice modules, and digital devices such as laptops and mobile phones. Participants consisted of 16 students, including 7 students from grade 1 and 9 students from grade 5. Evaluation employed a one-group pre–post design to measure changes after the intervention. The results showed improvements in grade 1 students’ pre-literacy skills, with letter recognition increasing from 8% to 48%, differentiation between uppercase and lowercase letters from 5% to 42%, and word copying skills from 10% to 40%, although beginning reading ability remained relatively low (from 5% to 16%). For grade 5 students, the average digital literacy score increased from 32 to 58, the proportion of students able to complete ANBK practice packages rose from 5% to 35%, and overall learning mastery improved from 8% to 38%. These findings indicate that mentoring-based ANBK training within a community service framework is effective in strengthening basic literacy and digital literacy foundations and improving elementary school students’ readiness for computer-based assessments.